Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s00300-016-2018-7
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of ivory gulls (Pagophila eburnea) at four colonies in Svalbard in relation to their trophic behaviour

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…A previous study on the ivory gull found that birds from Sigden displayed significantly different isotopic values in red blood cells compared with other colonies on Barentsøya (Lucia et al 2016).…”
Section: Relationship Between Trophic Position Feeding Habitat and Tmentioning
confidence: 88%
“…A previous study on the ivory gull found that birds from Sigden displayed significantly different isotopic values in red blood cells compared with other colonies on Barentsøya (Lucia et al 2016).…”
Section: Relationship Between Trophic Position Feeding Habitat and Tmentioning
confidence: 88%
“…In addition, Samecka-Cymerman et al (2011) report the highest concentration of Mn in S. uncinata from sites closest to the shoreline and thus most influenced by sea spray as well as from sites influenced by birds. Because of their high position in the nutritional chain, seabirds concentrate high levels of trace elements in their tissues (Lucia et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For our budgeting scenario, we planned the costs required to operate a field research camp for 4 weeks with three people (the lead researcher and two volunteers; this avoided cost issues related to pay scales), set to monitor the breeding success of seabirds (similar to Gaston et al 2005;Frederiksen et al 2014;Lucia et al 2016). We assumed that the site was a new location for the research team, such that there would not be food or fuel there already, but that a cabin would be there if that was required for safety.…”
Section: Methodsmentioning
confidence: 99%